Loss of smell and taste: a new marker of COVID-19? Tracking reduced sense of smell during the coronavirus pandemic using search trends. Issue 11 (1st November 2020) - Cherry, George; Rocke, John; Chu, Michael; Liu, Jacklyn; Lechner, Matt; Lund, Valerie J.; Kumar, B. Nirmal
ABSTRACT: Objectives: It has been demonstrated that reduction in smell and/or taste is the most predictive symptom in SARS-CoV-2/Covid-19 infection. We used Google Trends to analyze regional searches relating to loss of smell and taste across Italy, Spain, France, Brazil, and the United States of America and determined the association with reported Covid-19 cases. Methods: In order to retrieve the data, we built a Python software program that provides access to Google Trends data via an application program interface. Daily COVID-19 case data for subregions of the five countries selected were retrieved from respective national health authorities. We sought to assess the association between raw search interest data and COVID-19 new daily cases per million for all regions individually. Results: In total, we yielded 2188 sets of Google Trends data which included 548 time series of 4 anosmia and ageusia search concepts over the study period for 137 regions. These data indicated that differences in search interest for terms relating to anosmia and ageusia, between regions, is associated with geographical trends in new Covid-19 cases. Conclusions: We feel that Google search trends relating to loss of smell can be utilized to identify potential Covid-19 outbreaks on a national and regional basis.